Application of Silver Conducting Glasses to Solid State Batteries and Sensors - Liu Jun; J. Portier; B. Tanguy; J. J. Videau; M. Ait Allal; J. Morcos; J. Salardenne (Active and Passive Electronic Components)
Fast silver ion conducting glasses as electrochemical devices have been tested. A silver iodine battery using a silver ionic conducting glass (AgPO3-Ag2S-AgI) has been studied. The interaction of some gases (O2 CI2, H2S) with the electrochemical chains: Pt/Sb2S3-AgI (glass)/Ag and Pt/AgCl (thin film)/Sb2S3- AgI (glass)/Ag has been investigated. Finally, the behavior of thin films of Ag2S3-Ag2S-CdS glasses as sensitive membranes for Cd detection in solution has been tested on MIS structures Au/Si/SiO2/ Membrane/Cd in solution/Reference electrode.